The experience of 'feeling fat' in women with anorexia nervosa, dieting and non-dieting women: an exploratory study. - Cooper, M; Deepak, K; Grocutt, E; Bailey, E (2007)
OBJECTIVE: To provide a preliminary, systematic exploration of some features associated with the experience of 'feeling fat'. METHOD: Women with anorexia nervosa (N = 16), women who were dieting (N = 15) and non-dieting women (N = 17) took part in a semi-structured interview. RESULTS: Feeling fat was common in all three groups of women. It was associated with distress, negative emotions, internal and external body sensations, images in a range of modalities, negative self beliefs and a first memory of feeling fat. Differences specifically characteristic of those with anorexia nervosa were identified, including feeling fatter, greater associated distress, more negative emotions, greater 'emotional' belief in cognitions, a richer experience, an earlier first memory, greater strength of negative self beliefs and a link to restricting behaviour. Some qualitative data are reported. CONCLUSIONS: The experience of feeling fat can be 'unpacked' in a way that may be useful in cognitive therapy for those with anorexia nervosa.